The synthesis and Co(II), Co(III), Cu(II), Ni(II) and UO2(VI) complexes of a new symmetrical vic-dioxime containing 1,3-dioxolane - Tas, E; Çukurovali, A; Kaya, M (Gordon Breach Sci Publ Ltd, 1999)
9,10-bis(hydroxyimino)-4,8,11,15-tetraaza-1,2,17,18-O-dibenzal octadecane (LH2) was synthesized starting from 1,2-O-benzal-4-aza-7-aminoheptane, which was prepared from reaction of 1-chloro-2,3-O-benzal propane and dichloroglyoxime. The structure of this novel vicinal (vic) dioxime has been determined as the (E, E) form by H-1 NMR, C-13 NMR and IR data. Mononuclear complexes with a metal-ligand ratio of 1:2 have been prepared with Co(II), Cu(II) and Ni(II). In the case of uranyl, UO2(VI) salt was used and the metal-ligand ratio was found to be 1:1. In addition, a Co(III)(py)Cl complex of the ligand was prepared with pyridine (py) and chloride as axial ligands. The structures of the ligand and its complexes are proposed based on elemental analysis, IR,H-1 NMR and C-13 spectra, magnetic susceptibility measurements, thermogravimetric analyses (TGA) and differential thermal analyses (DTA).
Keywords: vic-dioxime; 1,3-dioxolane; cobalt(II and III); copper(II); nickel(II)